Estimation of the Level of Klotho Protein, Hemoglobin, and D- Dimer Factor in Obese Persons in Salah Al-Din Governorate - Saleh, Shaimaa Ahmed (American Journal of Bioscience and Clinical Integrity, 2026)
This study was conducted to determine the effect of obesity on vital biomarkers (cloth protein, MCHC, and D-dimer) by using 60 blood samples consisting of 40 samples from an obese group and 20 samples from a healthy group. Whether it was significantly lower in obese than in healthy individuals clofaslan D-dimer was assayed, and appeared to be higher (all p These changes suggest that obesity is associated with increased inflammation and oxidative stress, impaired oxygen transport, and a higher tendency for thrombosis. Hence, this study validates that obesity has a negative impact on various key physiological functions and is associated with an increased risk for cardiovascular diseases and blood disorders.